PENGARUH TINGGI RENDAHNYA PEMBELIAN DENGAN MELIHAT PEMBELIAN KEMBALI KONSUMEN - Osell Anindya Ayu Aldiona; I Made Sukresna (Jurnal Akuntansi dan Pajak, 2023)
The coffee shop business are a potential business in Indonesia due to the coffee shop business are currently experience high increase and increasing consumer interest. Starbucks coffee is one of the famous coffee shop especially in Indonesia. Primary data was used for data source in this research. The sampling technique is non probability sampling by accidental sampling. Measurement of the questionnaire used is Likert scale. This research was used Structural Equation Modeling (SEM) technique with Smart PLS 3 for software. The result of this study showed loyalty brand has a bigger effect on repurchase intention; and then brand awareness has a positive effect on repurchase intention; brand associations has a positive effect on repurchase intention; perception of quality has a positive effect on repurchase intention. Keywords : Loyalty Brand, Brand Association, Brand Awareness, Perception of Quality, Repurchase Intention.